2001
DOI: 10.1128/aem.67.11.5113-5121.2001
|View full text |Cite
|
Sign up to set email alerts
|

Denaturing Gradient Gel Electrophoresis Analysis of the 16S rRNA Gene V1 Region To Monitor Dynamic Changes in the Bacterial Population during Fermentation of Italian Sausages

Abstract: In this study, a PCR-denaturing gradient gel electrophoresis (DGGE) protocol was used to monitor the dynamic changes in the microbial population during ripening of natural fermented sausages. The method was first optimized by using control strains from international collections, and a natural sausage fermentation was studied by PCR-DGGE and traditional methods. Total microbial DNA and RNA were extracted directly from the sausages and subjected to PCR and reverse transcription-PCR, and the amplicons obtained we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
178
0
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(201 citation statements)
references
References 28 publications
14
178
0
9
Order By: Relevance
“…The single species detected in Karakačanski skakutanac cheese indicated that most probably only the dominant species was amplified. It has been reported that the detection limit of culture-independent PCR-DGGE, with the use of universal bacterial primer, is 10 4 cfu·g −1 [2,8]. Similar results have also been observed in PCR-DGGE analysis of an artisanal Robiola di Roccaverano cheese.…”
Section: Resultssupporting
confidence: 76%
“…The single species detected in Karakačanski skakutanac cheese indicated that most probably only the dominant species was amplified. It has been reported that the detection limit of culture-independent PCR-DGGE, with the use of universal bacterial primer, is 10 4 cfu·g −1 [2,8]. Similar results have also been observed in PCR-DGGE analysis of an artisanal Robiola di Roccaverano cheese.…”
Section: Resultssupporting
confidence: 76%
“…Theo ước tính chỉ có khoảng hơn 1% các vi sinh vật có thể nuôi cấy được [6].Trong những năm gần đây, nhờ sự phát triển của các phương pháp mới, tiên tiến việc xác định các loài vi sinh vật trở lên hiệu quả và nhanh chóng. Một trong các phương pháp đó là PCR-DGGE đã được sử dụng để quan sát động thái của vi khuẩn trong quá trình lên men bánh mỳ ở Mexicô [7,1], lên men xúc xích Ý [8,9], phomat [10,11,12,13]. Hơn thế nữa, DGGE cho phép phân tích đồng thời nhiều mẫu và so sánh quần thể vi sinh vật dựa vào sự khác nhau về địa lí [14].…”
Section: Mở đầUunclassified
“…The DNA extracted from the samples was PCR amplified as described previously (Mills et al, 2003) using four sets of fluorescently labeled universal eubacterial primers for the Idaho samples and one set for the Chesapeake samples. The 16S rRNA gene primers for the four hypervariable regions were as follows: for region V1 + V2, 6-FAM-27F and 355R (Suzuki et al, 1998); for region V1, 6-FAM-P1F and P1R (Cocolin et al, 2001); for region V3, HEX-338F and 518R (Cocolin et al, 2001); for region V9, NED-1055F and EC1392R (Cocolin et al, 2001). …”
Section: Data Setsmentioning
confidence: 99%